FUNCTIONAL-PROCESS MODELING OF REGULATORY SYSTEMS IN E-COMMERCE - Русин-Гриник, Роман; Залуцький, Юрій; Федина, Ярослав (SWorldJournal, 2023)
It has been proven that the regulatory system in e-commerce is a complex and multifaceted structure with various functions and properties. It is argued that among the main functions of the regulatory system are ensuring compliance with legislation, manag